Applying Theory of Planned Behavior to Understand Physicians’ Shared Decision-Making With Patients With Acute Respiratory Infections in Primary Care: A Cross-Sectional Study - Wang, Dan; Zhang, Xinping; Chen, Haihong; Liu, Chenxi (Frontiers in Pharmacology, 2022)
Abstract Background: To understand the physicians’ shared decision-making behavior (SDM) with patients with acute respiratory infections (ARIs) based on the theory of planned behavior (TPB) and identify barriers to the implementation of SDM in primary care. Methods: A cross-sectional study of 617 primary care physicians was conducted in primary facilities in Hubei province, China from December 2019 to January 2020. A self-administered questionnaire based on TPB theory was applied for measuring the physicians’ SDM behavior with patients presenting with ARIs. Results: The proposed TPB model revealed that attitude and subjective norms predicted behavior intention, and behavior intention was one significant predictor of SDM behavior(p<0.001). After controlling for physicians’ demographic characteristics, receiving training regarding antibiotics was significantly associated with physicians’ attitudes towards SDM, while educational level and gender were significantly associated with physicians’ intention of engaging in SDM (p<0.05). Physicians’ perceptions of patients’ expectations and incapability of making decisions were the most frequently reported barriers to the implementation of SDM. Conclusions: The TPB theory provides insights for understanding physicians’ SDM behavior with patients with ARIs in primary care. Since attitudes, subjective norms, and behavior intention were demonstrated as significant predictors of SDM behavior, these may be a promising focus of SDM interventions based on TPB theory. The results of the TPB model and potential barriers of SDM behavior would help determine future directions for SDM training and educating the public.